Factors influencing the behavior of pregnant women towards using prenatal care services in Iranian healthcare centers - Parisa Parsa; Fereshteh Besharati; Saeedeh Haji Maghsodi; maryam afshari; Shohreh Emdadi (Mashhad University of Medical Sciences, 2018)
Background & aim: Care provision is one of the most important factors in preventing and reducing mortality among pregnant mothers. Despite availability, the uptake of health services in health centers is undesirable. This study aimed to investigate the factors influencing the behavior of pregnant women towards using prenatal care services based on health belief model in healthcare centers of Tuyserkan, Hamadan Province, Iran. Methods: In this descriptive, analytical, cross-sectional study, 165 mothers visiting the health care centers of Tuyserkan, Hamadan Province, Iran, 1-15 days postpartum were chosen using the convenient sampling method during 2015. A self-structured questionnaire comprising items on demographics, knowledge, and health belief model constructs was employed for data collection. The data were analyzed using Pearson correlation coefficient, independent t-test, and logistic regression. Results: The study revealed that 72.1% of the pregnant women had regular visits, while 27.9% had irregular visits. Logistic regression reflected that knowledge (OR=0.929) and self-efficacy (OR= 0.976) were effective variables on regular prenatal visits. Conclusion: Considering pregnant women's physiological and anatomical conditions, prenatal care and regular visits are essential; thus, effective interventions in this area should be planned and implemented.